Wellness portal: e-Mailing and charting module / Jaime Chia Wai Ling - Jaime Chia , Wai Ling (2003)
Wellness portal is a web based wellness center developed for use of all walks of life from birth to senior citizen. Wellness Portal is designed to create an information rich environment of wellness resources, that is accessible and available. The users of the portal are categorized into 3 main groups: Normal Members, Advanced Members and Wellness Administrators. The Wellness Portal includes 5 modules that are Medical Screening, Exercise, Stress Management, Nutrition and Safety. They were divided into 5 age groups, Peadiatric, Adolescent, Young Adult, Prime Of Life and Golden Age. The Medical Screening is currently available for women in the age group of 40-60 years old. The members and wellness administrators need to logon to the system before using the portal Wellness Portal is developed using Microsoft Active Server Pages. NET (ASP.NET). The others development tools include Microsoft SQL Server 2000 with ADO.NET data access technology. We are using their-tier architecture in developing the portal. The browsers that support VBscript and JavaScript such as Internet Explorer 6.0 can support the Wellness Portal. Wellness Portal is expected to have security checking for authorized user, develop databases to keep all the records and creation of interactive homepages to deploy information to users. Wellness administrators will be maintaining the portal by tracking all activities in the portal.